Analysis of Line Balancing using Ranked Positional Weight (RPW), Largest Candidate Rule (LCR), and J-Wagon Methods in Crane Girder Production at PT MHE Demag Surabaya, Indonesia - Farida Pulansari; Isna Nugraha (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Every company is required to enhance its quality by implementing improvement actions within the company's production system. PT MHE Demag Surabaya is a company engaged in crane girder manufacturing. This research aims to determine the optimal line balancing using the Helgesson-Birnie/Ranked Positional Weight (RPW) method, the Largest Candidate Rule method, and the J-Wagon method. Line balancing is necessary due to excess operating time in the crane girder manufacturing workstations, which increases the risk of accidents for the workers. The results of data processing which employed these three heuristic methods demonstrate that the RPW method is the most efficient. The Helgesson-Birnie/Ranked Positional Weight (RPW) method yields the most optimal output, with a line efficiency of 96.67%, balanced delay of 3.33%, and total idle time of 4936.8 seconds using 15 workstations. By utilizing the heuristic methods for line balancing, the efficiency decreases to 144.76%, the balanced delay increases to 14.76%, and the total idle time increases to 86,400 seconds.